Pathological and Molecular Characterization of Grass Carp Co-Infected with Two Aeromonas Species - Wenyao Lv; Zhijie Zhou; Lingli Xie; Xinyue Wang; Yifei Zhou; Lang Gui; Xiaoyan Xu; Yubang Shen; Jiale Li; Junqiang Qiu (Animals)
The grass carp (Ctenopharyngodon idella) is highly susceptible to infections caused by Aeromonas species, particularly A. hydrophila and A. veronii. However, the immunological mechanisms underlying co-infection by these pathogens remain largely uncharted. This study investigated the pathogenesis and host immune response in grass carp following concurrent infection with A. hydrophila and A. veronii. Mortality was observed as early as 24 h post-infection, with cumulative mortality reaching 68%. Quantitative analysis demonstrated significantly elevated bacterial loads in hepatic tissue at 3 days post-infection (dpi). Histopathological evaluation revealed severe hepatic lesions characterized by cellular necrosis, cytoplasmic vacuolization, and hemorrhagic manifestations. Comparative transcriptomic analysis of hepatic tissues between co-infected and control specimens identified 868 and 411 differentially expressed genes (DEGs) at 1 and 5 dpi, respectively. Gene ontology and KEGG pathway analyses revealed significant enrichment of immune-related genes primarily associated with Toll-like receptor signaling and TNF signaling cascades. Notably, metabolic pathways showed substantial suppression while immune responses were significantly activated after infected. These findings provide novel insights into the host–pathogen interactions during Aeromonas co-infection in grass carp, which may facilitate the development of effective prevention and control strategies.